Temperature Dependency of Steady, Dynamic, and Creep-Recovery Rheological Properties of Ice Cream Mix - Toker, Omer Said; Karaman, Safa; Yuksel, Ferhat; Dogan, Mahmut; Kayacier, Ahmed; Yilmaz, Mustafa Tahsin (SPRINGER, 2013)
In this study, effect of processing temperature (5, 15, 25, and 35 A degrees C) on the steady, dynamic, and creep recovery rheological properties of the ice cream mix (ICM) was investigated. It was found that processing temperature significantly affected all rheological parameters of the ICM sample. The flow behavior of the ICM sample was fitted to the Ostwald de Waele model. The magnitude of storage modulus (G') was higher than that of loss modulus (GaEuro(3)) indicating that ICM sample had weak gel-like structure. Modified Cox-Merz rules were satisfactorily applied to the ICM sample to observe relationship between steady and dynamic shear properties. Additionally, Burger model was used to characterize the viscoelastic properties of the ICM sample. The gel strength (S) value was also calculated, and a decrease was observed with the increase of temperature. Arrhenius equation satisfactorily described the temperature dependency of the rheological parameters such as apparent viscosity at 50 s(-1) (eta (50)), consistency coefficient (K), the instantaneous shear modulus of the Maxwell unit (G (0)), permanent deformation (J (a) ), and S values that may be predicted by using established equations depending on the temperature. The increase in processing temperature caused a decrease in resistance of the mixture subjected to the deformation, which is very important for production of high quality ice cream.
Keywords: Ice cream mix; Temperature; Steady and dynamic rheology; Creep and recovery; Gel strength; Arrhenius equation; HOT CHOCOLATE BEVERAGE; VISCOELASTIC PROPERTIES; SENSORY PROPERTIES; FLOW PROPERTIES; XANTHAN GUM; BEHAVIOR; STARCH; MODEL; WHEAT; PARAMETERS; Food Science & Technology